Near-infrared spectroscopy of shocked molecular hydrogen in star formation regions - Fernandes, Amadeu Joaquim Lima (The University of Edinburgh, 1993)
The work presented in this thesis is devoted to the study of the physics of shock waves in the dense molecular cloud environments that are typical of star forming regions. The structure of these shock waves are analysed in terms of the two basic models: J-shock and C-shock.

We have investigated the H2 emission properties from Herbig-Haro 7 and the DR21 bipolar outflow by measuring several spectral lines arising in the K band. These H2 lines cover a wide range in energy of the upper level (6000—25000 K) and enables a detailed study of the temperature distribution of the gas. The calculated column density ratios have been compared to J and C-shock models for different shock geometries. We have shown that current oblique J- and C-shock models fail to explain the observed H2 column density ratios. J-shock models fail to provide sufficient hot gas from behind the shock front and are not able to explain the large line intensities observed in the high-vibrational H2 lines. The line emission from the 6 positions observed within the HH 7 bow are shown to be consistent with a paraboloidal bow shock geometry, which however necessitates of an extra source of excitation of the high energy levels to explain the H2 line ratios. We present a study of the effects of the UV radiation field associated with the bow shock structure and show that a shock-induced Far-UV radiation field with a strength of Go = 102-103, can account for the observed H2 line ratios. We suggest that shocks are responsiblefor the low-lying level excitation of the H2 molecule while Lya resonance pumping is responsible for the high-excitation line emission.

Measurements of several infrared emission lines of H2 in the K window from the DR21 bipolar outflow, show different excitation conditions for the east and west lobes of H2 emission. The higher H2 line ratios measured for the east lobe is indicative of enhanced excitation for the high-excitation levels of the H2 molecule,which can be caused by either shock-produced Lya resonance pumping or by direct UV excitation of H2 from the central Hn region. This is consistent with the east lobe being bordering the central Hn region and producing higher fluorescent fluxes We show that the H2 emission can be explained in terms of a model consisting of a C- shock and a PDR. The H2 line ratios are best fitted with a PDR model withparameters: FUV field in the range 102 < Go < 103 and densities n > 3 x 103 cm-3..

We show that the H2 fluorescent emission from both HH 7 and DR21 is reproduced better with an ortho to para ratio of 1.8.